Effect of heat conditioning and intermittent warming on chilling injury and pectolytic enzymes in peaches - MAO Lin-chun; ZHANG Shang-long (浙江大学学报. 农业与生命科学版, 2001)
About 86% peach fruit (Prunus persica, cv. Baifeng) became woolly during a ripening period of 4 d at 20℃ following 29 d of cold storage at 0 ℃. Conditioning at 35℃ for 48 h prior to cold storage or warming at 20℃ for 24 h every 9 d of cold storage was highly effective in alleviating woolliness, although low sensory quality or flesh softening also occurred. Browning was not always accompanied with the development of woolliness, but retention of flesh firmness was a typical woolliness symptom. Extractable juice content was highly negatively correlated with the incidence of woolliness. Endo-PG activity in fruit cold-stored immediately and continuously after harvest was low throughout storage and the subsequent ripening period. Both heat conditioning and intermittent warming enhanced PE, endo-PG and exo-PG activities, with the second intermittent warming being the most effective. Chilling injury development appeared to be associated with reduced endo-PG activity.